Analisis Pemasaran Kelapa Sawit Rakyat Dengan Model Structure Conduct And Performance (SCP) Di Kabupaten Labuhanbatu Utara - Openius Zai; Muhammad Buhari Sibuea; Apip Gunaldi Dalimunthe (Jurnal Ilmiah Pertanian ( JIPERTA), 2023)
The purpose of this study was to analyze the performance marketing system for the smallholder oil palm market in North Labuhanbatu District using a structure, conduct and performance approach to: (1) Analyze the structure of the palm oil market in North Labuhanbatu District. (2) Analyzing the behavior of the people's palm oil market in North Labuhanbatu District. (3) Analyzing farmer's margin and farmer's share in order to know the performance of the people's palm oil market in North Labuhanbatu Regency. The data analysis method used in this study is the analysis of market structure as seen from market share, market concentration and barriers to market entry. Analysis of market behavior seen from marketing channels and marketing mix 7P (product, price, place, promotion, people, process, physical evidence). Analysis of market performance seen from the marketing margin, farmer's share and marketing efficiency.Based on the results of research conducted, the structure of the smallholder palm market in North Labuhanbatu District shows a market share at the farmer level of 0.76%, 16.66% for collector traders and 82.63% for wholesalers at the farmer level and market collectors are perfect competition , while large traders are tight oligopoly markets. Market concentration at the farm level with a CR4 value of 76.70%, collector traders with a CR4 value of 71.07%, and wholesalers (PKS) with a CR4 value of 100% at market concentration at the farmer level and market collectors are strictly oligopoly , while large traders are monopolistic markets. Meanwhile, the MES value at the farm level is 49.43%, for collectors is 24.80%, while for wholesalers it is 100% so that it can be said that the barriers to market entry are high. The behavior of the people's palm oil market in North Labuhanbatu Regency can be seen from its marketing channels, there is only one marketing channel. There are several marketing institutions, namely farmers, collectors and wholesalers (PKS). Then it can be seen from the 7P marketing mix, in the marketing of smallholder oil palm in North Labuhanbatu Regency in accordance with the agreements made by farmers, collectors and wholesalers.Analysis of market performance (Market Performance) of smallholder oil palm in North Labuhanbatu District shows that there are 3 marketing channels with different margins. The highest total margin is in marketing channel III, which is Rp. 5,720/Kg, the more marketing agencies involved, the higher the marketing margin and the lower the farmer's share. The most efficient marketing channel is marketing channel I (large farmer-trader)